Kartagener’s syndrome: a rare case report - ., Supreety; Singh, T. Dinesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Kartagener's syndrome is an autosomal recessive primary ciliary dyskinesia. It is due to ciliary dysfunction consisting of triad of situs inversus, bronchiectasis, chronic sinusitis. Normal ciliary function is critical for respiratory host defence, motility of sperm and ensures proper visceral orientation during embryogenesis. In Kartagener syndrome, the gene mutation is at DNAI1 and DNAH5 leading to pathophysiological changes like ciliary immobility causing accumulation of secretions and consequent recurrent sinusitis. The severity of symptoms and the age at which the condition is diagnosed is quite variable, even though the symptoms are present from birth. We are reporting a case of 12-year-old male who came to ear, nose and throat outpatient department (ENT OPD) with complaints of bilateral nasal obstruction for the past 6 years associated with bilateral mucopurulent nasal discharge, having pale, greyish white polyps filling bilateral nasal cavities. Clinical examination and imaging findings revealed ethmoidal polyposis with chronic sinusitis, bronchiectasis, and situs inversus totalis. Patient underwent revision endoscopic intranasal ethmoidectomy with functinal endoscopic sinus surgery.